Initial Impressions and Review of Literature Concerning Factors Affecting the Use of Palliative Care Assessment Tools in an African Setting - John K. Weru (Palliative Medicine and Hospice Care, 2015)
Introduction: Quality palliative care encompasses early identification and impeccable assessment and treatment of pain and other problems, physical, psychosocial and spiritual.1Despite the importance of symptom assessment in palliative care, use of assessment tools in practice is limited.2 The aim of this study was to assess factors that influence use of symptom assessment tools. Methodology: 1:1 interviews were conducted using a guideline developed by the researcher. Ten participants who met the inclusion criteria were interviewed. The data was recorded and then transcribed with topics and issues being isolated and grouped together into themes. Findings: The themes were perception of palliative care, communication, practical concerns and emotions associated with use of assessment tools, spirituality and cultural compatibility with assessment tools, resources, policies and training. Conclusion: Lack of quality education in palliative care coupled with incompatibility of current tools with cultural and religious practices is a major hindrance to use of assessment tools. Poor communication among clinicians negatively affects use of assessment tools.